Visual cortical LFP in relation to the hippocampal theta rhythm in track running rats - Kennedy, Jack P.; Zhou, Yuchen; Qin, Yu; Lovett, Sarah D.; Cooper, Tara; Sheremet, Alex; Burke, Sara N.; Maurer, Andrew P. (Frontiers in Cellular Neuroscience, 2023)
Theta oscillations in the primary visual cortex (VC) have been observed during running tasks, but the mechanism behind their generation is not well understood. Some studies have suggested that theta in the VC is locally generated, while others have proposed that it is volume conducted from the hippocampus. The present study aimed to investigate the impact of hippocampal LFP on LFP in the VC. Analysis of power spectral density revealed that LFP in the VC was similar to that in the hippocampus, but with lower overall magnitude. As velocity increased, both the power and frequency of theta and its harmonics increased in the VC. However, the increase in theta frequency in the VC was similar to that in the hippocampus and was not significantly different between the two. Current source density analysis triggered to theta did not identify distinct current sources and sinks in the VC, supporting the idea that theta in the VC is conducted from the adjacent hippocampus. Phase coupling between theta, its harmonics, and gamma is a notable feature in the hippocampus, particularly in the lacunosum moleculare. While some evidence of coupling between theta and its harmonics in the VC was found, bicoherence estimates did not reveal significant phase coupling between theta and gamma. Similar results were seen in the cross-region bicoherence analysis, where theta showed strong coupling with its harmonics with increasing velocity. The present study found evidence that theta oscillations observed in the VC during running tasks are likely due to volume conduction from the hippocampus and includes discussion of anatomical interactions.